METAPHOR ANALYSIS OF TWO INTERNATIONAL BURGER FRANCHISES - Ronald Maraden P. Silalahi; Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2022)
Burger King and McDonald's are the two largest burger franchises globally, characterized by the number of restaurants owned. Burger King and McDonald's competition can be seen from how the two companies penetrate the global market. From the advertising context, both companies innovatively and persuasively develop consumer awareness on the one hand, and on the other hand, there are attempts to weaken competitors. This research is directed to analyze the (multimodal) metaphor used by the two companies to promote burger products. Qualitative research on pictorial advertisements was carried out in stages through several phases, which included descriptions of social, historical, and cultural contexts, identification of visual elements, identification of verbal elements, and analysis that elaborated on the three phases. The analysis shows competition between Burger King's and McDonald's advertisements. Multimodal metaphor analysis comprehensively shows that both companies use visual and verbal elements to increase consumers' awareness of existing or future products. Both companies tend to use personification to build corporate identity and the products offered and will be promoted. This research still has many weaknesses. The author suggests that the analysis focus on linguistic elements and extra-linguistic elements, such as motion, images, and sounds.